Travailler en circuits courts : des exploitations sous tensions - Jean-Baptiste Paranthoën; Pierre Wavresky (La Nouvelle Revue du Travail)
In contrast to some unified vision where farms are often depicted as being part of short-distance supply chains, the article offers a sociological analysis of entrepreneurial activity in this domain and questions the way in which tensions between productive and commercial tasks are actually arbitrated. Combining a statistical treatment of France’s 2010 agricultural census with a 7-year ethnographic survey of 14 farms, it reveals three possible categorisations: intermittent farms, where marital roles determine the division of labour; specialist farms, fully involved in short-distance supply chains and based on a weak division of labour; and diversified farms, characterised by a partial delegation of commercial skills.